The relationship between macroeconomic factors and tourism demand for ASEAN countries - Saizal Pinjaman; Marry Tracy Pawan (Human Resource Management Academic Research Society, 2021)
The current paper investigates the relationship between macroeconomic factors and tourism demand for nine selected ASEAN countries. Based on the panel data analysis, it is identified that income is positively related to tourism demand where an increase in the level of income for ASEAN leads to higher tourist arrival to the region. The income is also shown to be the most important factor that determines tourism demand as demonstrated by the high coefficient value in the estimation. The appreciation of ASEAN currencies meanwhile is identified to discourage tourists from visiting the region and on the other hand, trade openness stimulates the demand as it implies the ease of entry. Since majority of the tourist came from developed countries with high purchasing power, price level is identified to be not significant in explaining the movement of tourism demand in the region. To develop the tourism sector, proper plans should be made including to improve the infrastructure, tourism facility and travel safety, and ease of entry considering the positive impact of economic development and trade openness. Relevant strategies should also be made to attract tourists from countries with higher purchasing power and strong currency value since it implies to be important in explaining the movement of tourism demand.